2012
DOI: 10.1007/s00431-011-1666-4
|View full text |Cite
|
Sign up to set email alerts
|

The use of chloride–sodium ratio in the evaluation of metabolic acidosis in critically ill neonates

Abstract: Acid-base disturbances have been usually evaluated with the traditional Henderson-Hasselbach method and Stewart's physiochemical approach by quantifying anions of tissue acids (TA). It is hypothesized that an increase in tissue acids during metabolic acidosis would cause a compensatory decrease in the plasma chloride (Cl) relative to sodium (Cl-Na ratio) in order to preserve electroneutral balance. Therefore, we aimed to investigate the use of Cl-Na ratio as a bedside tool to evaluate the identifying raised TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
0
15
2
1
Order By: Relevance
“…We think that this notion is most important in septic patients who have increased mortality. Rare combinations can be seen in daily clinical practice, and those combinations were also discussed in previous studies (Table 3) (6,9,13,(15)(16)(17)(18)(19). Kurt et al (15) indicated the presence of hypochloremic metabolic acidosis in 16% of acid-base disorders.…”
Section: Classification and Calculationsmentioning
confidence: 77%
“…We think that this notion is most important in septic patients who have increased mortality. Rare combinations can be seen in daily clinical practice, and those combinations were also discussed in previous studies (Table 3) (6,9,13,(15)(16)(17)(18)(19). Kurt et al (15) indicated the presence of hypochloremic metabolic acidosis in 16% of acid-base disorders.…”
Section: Classification and Calculationsmentioning
confidence: 77%
“…This leads to a decrease in the chloride:sodium ratio, an increase in the SID, and thus a decrease in water dissociation and a fall in hydrogen ion activity (hypochloraemic alkalosis). Thus assessment of chloride, and in particular the chloride:sodium ratio, becomes of real value in determining the acid-base disturbance and assessing treatment in critically ill patients [33][34][35][36][37]. Assessment of SID can be used as a quantitative guideline for chloride (NaCl or KCl) replacement.…”
Section: Hydrogen/acid-basementioning
confidence: 99%
“…Le rapport Cl/Na, et, dans une moindre mesure, la différence [Na + ] -[Cl -] permettent d'évaluer la présence d'acides tissulaires, c'est-à-dire lactate et anions indosés, et constituent donc un substitut relativement fiable au TAPc, un rapport Cl/Na inférieur à 0,75 étant en faveur d'une augmentation d'acides tissulaires et un rapport supé-rieur à 0,79 excluant cette présence [45]. Enfin, il a été montré que le rapport Cl/Na a une bonne corrélation inverse avec le TAPc (r = -0,806), tandis que la différence [Na + ] -[Cl -] a une bonne corrélation « positive » avec le TAPc (r = 0,82) dans une population néonatale [46].…”
Section: éQuilibre Entre Na Et CLunclassified